Patient-reported outcomes after chemoradiotherapy for anal cancer - Kathinka Schmidt Slørdahl; Eva Skovlund; Jan-Åge Olsen; Ragnhild Tvedt; Maria Thomsen; Stein Kaasa; Marianne Grønlie Guren (Acta Oncologica, 2025)
Background and purpose: Chemoradiotherapy (CRT) for squamous cell carcinoma of the anus (SCCA) results in favorable survival. However, treatment intensity must be balanced against late side effects. The aim of this current study was to prospectively investigate patient-reported outcomes (PROs) before CRT and up to 5 years after completed CRT for SCCA.